Novel mutations in antiviral multiresistant HSV‐2 genital lesion: A case report. Issue 12 (20th August 2022) - Khellaf, Lucas; Bouscarat, Fabrice; Burrel, Sonia; Fidouh, Nadhira; Hachon, Lorry; Bucau, Margot; Lariven, Sylvie; Boutolleau, David; Joly, Véronique; Ghosn, Jade; Le Pluart, Diane; Thy, Michaël
Abstract: HSV‐2 antiviral resistance mainly occurs in immunocompromised patients and especially in HIV‐positive individuals receiving long‐term antiviral treatment. Those situations can be challenging as few alternatives are available for HSV infection management. To describe clinical and virological significance of two novel potential HSV‐2 resistance mutations after treating an obese patient with a pseudotumoral genital HSV‐related lesion. Consecutive different antiviral treatments were used: valacyclovir (VACV) then foscarnet (FOS) then topical cidofovir (CDV) and finally imiquimod. Under VACV, genotypic resistance testing revealed a novel mutation within viral thymidine kinase (TK, gene UL23) not previously reported but probably accounting for antiviral resistance: W89G, similar to W88R mutation reported in HSV‐1 TK, known to be associated with ACV resistance for HSV‐1. Under FOS, while initial mutations were still present, a second genotypic resistance testing performed on persisting lesions showed a novel mutation within viral DNA polymerase (DNA pol, gene UL30): C625R. All three antivirals used in this case are small molecules and pharmacokinetics of VACV, FOS, and CDV have not been evaluated in animals and there are very few studies in human. As small molecules are poorly bound to proteins and distribution volume is increased in obese patients, there is risk of underdosage. This mechanism is suspected to be involved in emergence of resistance mutation and further data is needed to adapt, closely to patient profile, antiviral dosage. This report describes a chronic HSV‐2 genital lesion, with resistance to current antivirals and novel mutations within viral TK and DNA pol which may confer antiviral resistance.